INFLUENCE OF THE MODERN SYSTEMS FOR ELECTRONIC EDUCATION ON THE MOTIVATION OF THE YOUNG PEOPLE TO TURN EDUCATION INTO A LIFELONG ACTIVITY (Innovation in Woodworking Industry and Engineering design, 2026)
The traditional forms of education used to answer the needs of the young people at a time when it was possible with a relative certainty to foresee the knowledge and skills from which they are going to need in the years of their mature life. Today it is not like this. The young people cannot expect already to spend their whole life in one and the same sphere of activity and even at one and the same place; their professional way is about to change in a way could not be foreseen, and they need a broad circle of common skills, which will let them adapt. In a more complex and globalized world the creative skills, the ability to think in a multifunctional way, the skills in different fields, and their adaptability as a tendency are valued more than the specialized knowledge.To answer these needs, it is necessary as part of the syllabuses on the disciplines, apart from the knowledge, which should be taught, to be given the results (the skills and the habits which are expected to be developed from the educated at different stages of their education).In the present research a theoretical framework for electronic education is introduced and the issue for discussion is: Could the modern systems for electronic education provide the young people with skills and motivation for the turning of education into a whole life activity?